Molecular Epidemiology and Antifungal Resistance of Cryptococcus neoformans From Human Immunodeficiency Virus-Negative and Human Immunodeficiency Virus-Positive Patients in Eastern China - Zhou, Ziyi; Zhu, Chendi; Ip, Margaret; Liu, Manjiao; Zhu, Zhaoqin; Liu, Ryon; Li, Xiaomin; Zeng, Lingbing; Wu, Wenjuan (Frontiers in Microbiology, 2022)
Cryptococcosis is an opportunistic and potentially lethal infection caused by Cryptococcus neoformans and Cryptococcus gattii complex, which affects both immunocompromised and immunocompetent people, and it has become a major public health concern worldwide. In this study, we characterized the molecular epidemiology and antifungal susceptibility of 133 C. neoformans isolates from East China Invasive Fungal Infection Group (ECIFIG), 2017-2020. Isolates were identified to species level by matrix assisted laser desorption ionization-time of flight mass spectrometry and confirmed by IGS1 sequencing. Whole-genome sequencing (WGS) was conducted on three multidrug-resistant isolates. Among the 133 strains, 61 (45.86%) were isolated from HIV and 72 (54.16%) from HIV-uninfected patients. In total, C. neoformans var. grubii accounted for 97.74% (130/133), while C. neoformans var. neoformans was rare (2.06%, 3/133). The strains were further classified into nine STs dominated by ST5 (90.23%, 120/133) with low genetic diversity. No association was observed between STs and HIV status. All strains were wild-type to voriconazole, while high antifungal minimal inhibitory concentrations (MICs) above the epidemiological cutoff values (ECVs) were observed in C. neoformans strains, and more than half of isolates were non-wild-type to amphotericin B (89.15 %,109/133). Eight isolates were resistant to fluconazole, and eight isolates were non-wild -type to 5-fluorocytosine. Furthermore, WGS has verified the novel mutations of FUR1 in 5-fluorocytosine resistant strains. In one isolate, aneuploidy of chromosome 1 with G484S mutation of ERG11 were observed, inducing high-level resistance (MIC: 32 μg/mL) to fluconazole. In general, our data showed that there was no significant difference between HIV and non-HIV patients on STs, and we elucidate the resistant mechanisms of C. neoformans from different perspectives. It is important for clinical therapy and drug usage in the future.